2014
DOI: 10.1371/journal.pone.0107057
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus-Based versus Cyclosporine-Based Immunosuppression in Hepatitis C Virus-Infected Patients after Liver Transplantation: A Meta-Analysis and Systematic Review

Abstract: BackgroundMost liver transplant recipients receive calcineurin inhibitors (CNIs), especially tacrolimus and cyclosporine, as immunosuppressant agents to prevent rejection. A controversy exists as to whether the outcomes of hepatitis C virus (HCV)-infected liver transplant patients differ based on the CNIs used. This meta-analysis compares the clinical outcomes of tacrolimus-based and cyclosporine-based immunosuppression, especially cases of HCV recurrence in liver transplant patients with end-stage liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Outcomes in the HCV subgroup analysis of graft loss were also in line with many individual RCTs and a 2014 meta-analysis by Liu and colleagues [14]. In terms of individual studies, Villamil et al .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Outcomes in the HCV subgroup analysis of graft loss were also in line with many individual RCTs and a 2014 meta-analysis by Liu and colleagues [14]. In terms of individual studies, Villamil et al .…”
Section: Discussionsupporting
confidence: 69%
“…and a 2014 analysis focusing specifically on patients with hepatitis C virus (HVC) [1214]. However, many of these analyses include data from older trials of tacrolimus and ciclosporin, predating either the use of ciclosporin microemulsion or the more prevalent use of MMF as the antiproliferative agent in place of the anti-metabolite azathioprine.…”
Section: Background and Aimsmentioning
confidence: 99%
“…While there are no models suggesting a percentage of recurrence‐free survival necessary to justify expansion criteria, this study had a 69% recurrence‐free survival at 5 years and 47% at 10 years, which was not statistically different from the 74% and 54% recurrence‐free survival observed at 5 and 10 years, respectively, in the MC group. Allograft survival can also be a potential issue in liver transplant recipients with history of HCC, as these patients require both chemotherapy and immunosuppression and there is a lack of standardization in the literature of which modalities are most advantageous . Our study demonstrated that allograft survival was not compromised using the expanded R4C, nor was it statistically different compared to the MC group, even when stratifying patients based on presence of pretransplant LRT.…”
Section: Discussionmentioning
confidence: 64%
“…Allograft survival can also be a potential issue in liver transplant recipients with history of HCC, as these patients require both chemotherapy and immunosuppression and there is a lack of standardization in the literature of which modalities are most advantageous. [20][21][22][23] This could, in part, be explained by the higher MELD score for R4C patients (25 vs 24, P = .001); however, further studies and investigations would need to be undertaken to fully explain this observation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact is most pronounced when high-intensity regimens are used to treat acute rejection, particularly with high-dose steroid boluses and anti-lymphocyte antibody preparations [11][12][13]. There are no convincing data to support the use of any specific induction or maintenance regimen, and it is likely that the choice of initial calcineurin inhibitor (tacrolimus or cyclosporine) does not significantly impact overall outcomes in HCV-positive liver transplant recipients [14].…”
Section: The Role Of Immunosuppressionmentioning
confidence: 99%